The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1002/bbpc.19860900520
|View full text |Cite
|
Sign up to set email alerts
|

The Observed and Calculated Vibrational Spectra of DL‐methionine in the Study of the Solid State Phase Transition

Abstract: The ir and Raman spectra of α and β‐DL‐methionine and three isotopomers have been recorded and assigned with the help of normal coordinate analyses. The vibrational intensities of three conformers (χ1 = gauche II; χ2 = trans; χ3 = gauche I, trans, and gauche II) have been calculated for the free molecule with a MNDO program including a finite field perturbation. Except for the vibrations including the S atom, the CO−2 and NH+3 group the calculations agree with experimental data and confirm the change of χ3 fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
(2 reference statements)
0
10
0
Order By: Relevance
“…The first ratio is assumed to be sensitive to lateral chain−chain interactions and the second ratio is sensitive to intermolecular interactions, but also it should reflect the mobility of the methyl terminal group of hydrocarbon chains. Thus, the lower the intensity ratio is, the higher the conformational order of the alkyl chain and the lower mobility of the methyl end group is obtained. ,, Figure represents the changes in Raman peak height intensity ratios in relation to temperature of dl -norvaline. It is shown clearly that there are two temperature regions at about −120 and −76 °C, in which an increase of the intensity ratios is observed that almost corresponds to the phase transitions observed by DSC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first ratio is assumed to be sensitive to lateral chain−chain interactions and the second ratio is sensitive to intermolecular interactions, but also it should reflect the mobility of the methyl terminal group of hydrocarbon chains. Thus, the lower the intensity ratio is, the higher the conformational order of the alkyl chain and the lower mobility of the methyl end group is obtained. ,, Figure represents the changes in Raman peak height intensity ratios in relation to temperature of dl -norvaline. It is shown clearly that there are two temperature regions at about −120 and −76 °C, in which an increase of the intensity ratios is observed that almost corresponds to the phase transitions observed by DSC.…”
Section: Resultsmentioning
confidence: 99%
“…This table summarizes conformationally sensitive bands which are showed differences during phase transition and will be discussed in the text. Bands were assigned by comparison with similar compounds. ,,,,,, ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figs. 3(a) and (b) show CH 3 -S stretching region and -COO-vibration region, respectively [2]. The spectra observed at 333 K are different from others, indicating that the structural change of the crystal occurred between 323 and 333 K.…”
Section: Resultsmentioning
confidence: 96%
“…Earlier infrared studies of methionine and selenomethionine, which utilized solid-state amino acids (Shepherd and Huber, 1969;Tamba et al, 1973), revealed that the S!Se substitution had a small effect on the 1800-1400 cm ÿ1 region but altered many peaks below 1400 cm ÿ1 . The latter bands represent various vibrational modes of the methionine side chain and typically have medium intensity (Grunenberg and Bougeard, 1986). Because our difference spectra exhibited only two bands at 1284 and 903/899 cm ÿ1 , which are sensitive to the S!Se replacement, it appears that only minor alterations of the chemical bonds involving sulfur occur during the BR!M transition.…”
Section: Model Compoundsmentioning
confidence: 99%